Association between Dental Caries, Obesity and Salivary Alpha Amylase in Adolescent Girls of Babol City, Iran-2017 - Marie Kor; Mahdi Pouramir; Soraya Khafri; Shima Ebadollahi; Samane Gharekhani (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Adolescents are at risk of obesity and caries due to various factors such as diet and poor health habits; these factors may affect their body mass index (BMI) and salivary components. Therefore, it is necessary to assess these factors and their relationship in this age group. Purpose: This study aimed to evaluate the association between decayed missing filled teeth index (DMFT), salivary alpha amylase (sAA) level and age-specific BMI in adolescent girls. Materials and Method: A cross-sectional study was conducted on 81 females aged 13-15 years in 3 groups of BMI percentiles; "normal", "at risk for overweight" and "overweight" (n=27). DMFT was calculated and unstimulated saliva samples were collected. The sAA level was measured with a spectrophotometer. Data were analyzed using Kolmogorov-Smir-nov test, Kruskal- Wallis and Spearman correlation tests using SPSS (version 23) at p< 0.05. Results: The concentration of sAA and mean DMFT were estimated 1326.56±4.73 U/L and 2.77±2.36, respectively. There was no significant difference in sAA level and mean DMFT among BMI groups. A positive and significant correlation was found between sAA and DMFT in overweight group (r: 0.46, p= 0.014). Conclusion: Within the limitation of this study, higher levels of sAA may be considered as an indicator for dental caries in overweight adolescent girls.